Futures studies of the strategy of knowledge-based companies with a scenario approach - Akbarpoor, Mohammad; Tizroo, Ali (Mudīriyyat-i rāhburdī-i dānish-i sāzmānī, 2022)
The ability to imagine what will probably happen is one of the most important characteristics of successful companies, and it will be even more so if this company is a knowledge-based company whose basis of competition and competitive advantage is based on knowledge. Therefore, in this research, an attempt has been made to formulate possible scenarios and, as a result, appropriate strategies for these companies, by looking ahead to competitive advantage components in knowledge-based companies. This research is applied in terms of purpose and in terms of method it is survey type and exploratory level. The statistical population of this research was made up of 97 managers and experts in 46 science-based companies located in Shiraz Chemical Industries Technology Town and Science-based Fatko Holding, which according to the type and stages of the research, groups of 15 people, 7 people and 6 people were selected judiciously. Investigating the literature of the first stage, 4 main political, strategic, economic, financial, socio-cultural and technological categories were selected by reviewing the subject literature, and then 30 components were identified by re-using the subject literature and interviewing experts, and then using the opinion of a group of 15 experts. And by Delphi method, 26 competitive advantage components were finalized. In the second stage, in order to determine the mutual effects of the components, these components were included in 2 questionnaires and a group of 7 experts completed them. One of these questionnaires was developed for use in MICMAC analysis and the other for use in Scenario Wizard software. The existence of the scenario in the output of the scenario wizard software and the reliability of 95% of the MICMAC questionnaire guarantees the validity and internal consistency of these 2 questionnaires and the relevant data.The results of the scenario wizard software provided 8 acceptable (strong) scenarios, among which 3 optimistic, pessimistic and most likely scenarios were analyzed. By categorizing the advantageous components into 4 political/strategic, economic/financial, social/cultural and technological categories, the results of the three scenarios were also presented in this category. In the last stage, a 6-person group was used to formulate the necessary measures and policies, and this group finally suggested 12 measures for the optimistic scenario, 9 measures for the probable scenario, and 4 measures for the pessimistic scenario. In general, it can be said that in knowledge-based companies, the distribution of knowledge management power towards the four categories of more production, market development, project result orientation and more quality can provide a favorable scenario to achieve the maximum use of facilities and opportunities.